I Assumed the Responsibility of Contraception from My Wife: A Vasectomy Acceptors Experience - Masrina Munawarah Tampubolon; Widyawati Widyawati; Budi Wahyuni (CV. Rayyan Dwi Bharata, 2024)
The phenomenon of the vasectomy contraception usage is such a complex experience. Each of community has its own uniqueness of cultures that forms men’s perspectives in selecting and using vasectomy contraception. This study aims at exploring the men’s experiences in using vasectomy contraception. Nine research participants participated in semi-structured interview for approximately 60 minutes. Triangulation sources were the acceptors’ wives and Keluarga Berencana (Family Planning) assistants. The finding of the study was transcribed and analysed through Colaizzi (1978) with Opencode software version 4.03. This study obtained three main themes including: vasectomy motivation; changes experienced after vasectomy as well as eases and challenges of vasectomy technology. This study found that vasectomy brings confidence for the acceptors, generates physical and psychological balance of acceptor pairs and it also presents positive construction in society. Vasectomy acceptors feel confident in relation to the positive image of a man as the family leader and become the example of it in society. Generally, vasectomy is a choice that satisfies pairs in which physical and psychological complaint is in absence.